The Lamin-Like LITTLE NUCLEI 1 (LINC1) Regulates Pattern-Triggered Immunity and Jasmonic Acid Signaling - Jarad, Mai; Mariappan, Kiruthiga; Almeida-Trapp, Marilia; Mette, Michael Florian; Mithöfer, Axel; Rayapuram, Naganand; Hirt, Heribert (Frontiers in Plant Science, 2020)
Pathogen-associated molecular pattern (PAMP) recognition occurs by plasma membrane located receptors that induce among other processes nuclear gene expression. However, signaling to the nuclear compartment is restricted by the nuclear envelope and nuclear pore complexes (NPCs). We show here that among the four Arabidopsis lamin homologs LITTLE NUCLEI/CROWDED NUCLEI (LINC/CRWN), LINC1 plays an important role in PTI and jasmonic acid signaling. We show that linc1 knock out mutants affect PAMP-triggered MAPK activation and growth inhibition, but not reactive oxygen species (ROS) or callose accumulation. We also demonstrate that linc1 mutants are compromised in regulating PAMP-triggered pathogen-related genes, in particular encoding factors involved in jasmonic acid (JA) signaling and responses. Expression of a number of JAZ domain proteins, the key JA-related transcription factor MYC2 as well as key MYB transcription factors and biosynthesis genes of both the indole and aliphatic glucosinolate (GS) pathways are changed in linc1 mutants. Moreover, PAMP triggers JA and JA-Ile accumulation in linc1 mutants, whereas salicylic acid (SA) levels are unchanged. Despite impairment in PAMP-triggered immunity, linc1 mutants still show basal immunity towards Pseudomonas syringae DC3000 strains. High JA levels usually render plants resistant to necrotrophic pathogen. Thus, linc1 mutants show enhanced resistance to Botrytis cinerea infection. In accordance with a general role of LINC1 in JA signaling, linc1 mutants are hypersensitive to growth inhibition to external JA. In summary, our findings show that the lamin-like LINC1 protein plays a key role in jasmonic acid signaling and regulation of PTI responses in Arabidopsis.